Analisis Cluster Hierarki Pada Tingkat Kemiskinan di Provinsi Sumatera Utara tahun 2023 - Bagus Candra Setiawan; Arum Nilawati; Rahmad Ferdian; Raihan Aditya Saputra; Yemima Putri Santoso; Muhammad Riefky (LogicLink, 2025)
Poverty is one of the problems that is still a priority in social and economic development in Indonesia. In 2023, North Sumatra Province had a poverty rate of 8.15% with a total of 1,239.71 thousand poor people. The condition of poverty by district/city in North Sumatra Province is very diverse. The purpose of this study is to group districts/cities in North Sumatra Province in 2023 based on poverty rate indicators using hierarchical clusters. The data used in this study is secondary data with four poverty variables from 33 districts/cities in the North Sumatra Province in 2023. The results of the analysis contained 3 clusters with the number of members in clusters 1, 2, and 3. Suggestions for the North Sumatra Provincial Government need to formulate adaptive and specific policies based on the characteristics of each regional cluster prioritizing high poverty problem areas through strengthening access to education, health, and productive economic development. In addition, intensive cooperation between regions within the same cluster should be developed to support information exchange, joint empowerment programs, and local economic development synergies to improve the effectiveness of interventions and the welfare of the community in a sustainable manner.